Crowdfunding Sebagai Penguatan Urban Farming Masyarakat Penjaringansari Surabaya Menuju Ekonomi Hijau - Setyaningrum, Idfi; Nur Achadijah; Kartini Kartini; Ramdan Hidayat (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2023)
To solve the challenges of the urban agriculture system, urban farming is a viable option. RT 02 RW 04, located in Penjaringansari Village, Rungkut Subdistrict, Surabaya City, is a group of urban dwellers attempting to survive in difficult circumstances. Vertical gardening (TOGA) development employing vertical farming methods has been chosen to preserve the environment and health. This activity intends to provide help and information transfer, particularly in the growth of TOGA (family medicinal plants) on restricted land as a more effective agricultural alternative. The aid covers planting media selection, seedling, planting, and harvesting. The Edu_DoIt approach (Education and Do It) is used in this community service project, which means education with direct application. The result of this activity is educational vertical gardening in limited spaces. The harvested produce is sold to the local community, providing not only knowledge but also sustainable economic value. This activity has led RW 04 Penjaringansari Surabaya to be nominated as one of the top 500 neighborhoods in Surabaya, demonstrating the residents’ commitment and hard work in improving their environment